IMPLEMENTASI PEMBELAJARAN DARING BAHASA INDONESIA DI SMP NEGERI 1 JEBUS BANGKA BARAT - Nadia Alifulia (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
The objectives of this study are: (1) to describe the Indonesian online learning implementation plan (RPP), (2) to describe the implementation system of online learning Indonesian. This study uses a descriptive method of interviews, observations, questionnaires, and documentation with a qualitative approach. Data collection techniques used listening techniques and note-taking techniques. The targets of this study were Indonesian language teachers and students in grades VII, VIII, and IX. The data obtained in the form of observations, interviews, student questionnaires, and documentation. The results of the study show that (1) the implementation plan for Indonesian online learning is adjusted to the RPP specifically for online learning Curriculum 2013 that has been provided by the Ministry of Education and Culture in accordance with Circular Number 14 of 2019 concerning "Simplification of the Learning Implementation Plan (RPP)", (2) the implementation system online learning using an interactive online learning model based on Zoom Meeting, Google Meeting, Google Classroom, WhatsApp, and so on. The teacher also applies a synchronous online learning model in order to create good interactions with students. Teachers also use expository and inquiry online learning strategies by applying discovery learning models and problem based learning because they adjust the constraints experienced by students.